2022
DOI: 10.1002/brb3.2771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of childhood trauma on nonsuicidal self‐injury in adolescent patients with bipolar II depression

Abstract: Objective: This study was performed to explore the effect of childhood trauma on nonsuicidal self-injury (NSSI) in adolescents with bipolar II (BD II) depression. Methods:Based on the diagnostic criteria of the DSM-5 and structured interviews to assess the presence or absence of NSSI, 184 adolescent patients with BD II depression were divided into the NSSI (n = 112) and non-NSSI (n = 72) groups. The Adolescent Nonsuicidal Self-Injury Assessment Questionnaire (ANSAQ), Childhood Trauma Questionnaire-Short Form (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…After controlling for all available covariates, emotional abuse continued to be an independent risk factor for NSSI in the CTQ-SF. This finding is in keeping with a previous study ( Zhang et al, 2022 ). Similar to our findings, Kang et al (2018) discovered that emotional abuse was a significant predictor of self-injury in a sample of Chinese adolescents.…”
Section: Discussionsupporting
confidence: 94%
“…After controlling for all available covariates, emotional abuse continued to be an independent risk factor for NSSI in the CTQ-SF. This finding is in keeping with a previous study ( Zhang et al, 2022 ). Similar to our findings, Kang et al (2018) discovered that emotional abuse was a significant predictor of self-injury in a sample of Chinese adolescents.…”
Section: Discussionsupporting
confidence: 94%
“…From the theory and our results, they will ght against negative emotions in unique ways, such as NSSI, to protect themselves. Second, different childhood traumatic experiences have different effects on depression and NSSI: Heleniak et al [46] found a strong association between childhood pleasure de cit mood disorder and child maltreatment in the sample of community adolescents; Zhang et al [25] found that the risk factor for NSSI was emotional abuse. Finally, there is a reciprocal predictive relationship between NSSI and depression in adolescents [47].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, depression and NSSI are heavily in uenced by childhood trauma. Some scholars have found that there is a signi cant positive correlation between childhood trauma and NSSI in general [24], while others have found that emotional abuse in childhood trauma is a risk factor affecting the physical and mental health development of adolescents [25]; Steine et al…”
Section: Introductionmentioning
confidence: 99%